2020
DOI: 10.3390/ijms21218364
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Active Peptides of Marine Origin with ACE Inhibitory Activities: Potential Role as Anti-Hypertensive Drugs and in Prevention of SARS-CoV-2 Infection

Abstract: Growing interest in hypertension—one of the main factors characterizing the cardiometabolic syndrome (CMS)—and anti-hypertensive drugs raised from the emergence of a new coronavirus, SARS-CoV-2, responsible for the COVID19 pandemic. The virus SARS-CoV-2 employs the Angiotensin-converting enzyme 2 (ACE2), a component of the RAAS (Renin-Angiotensin-Aldosterone System) system, as a receptor for entry into the cells. Several classes of synthetic drugs are available for hypertension, rarely associated with severe o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 116 publications
0
17
0
Order By: Relevance
“…Angiotensin-converting enzyme (ACE) catalyzes specific reactions involved in blood pressure regulation, which makes this enzyme responsible for hypertension and a key target in the therapy of such a risk factor of cardiovascular disease. Antihypertensive peptides obtained from seafood have been extensively reviewed elsewhere [ 63 ], demonstrating that the recovery of these bioactive compounds is an efficient way of using seafood by-products. For instance, some studies have shown that peptides obtained through collagen hydrolysis from skate skin and sea cucumber can inhibit the activity of angiotensin-converting enzyme (ACE) [ 12 , 13 , 14 ], being a natural and potentially healthier alternative to synthetic ACE inhibitors available on the market.…”
Section: Bioactive Properties Of Seafood Side Stream-derived Peptimentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin-converting enzyme (ACE) catalyzes specific reactions involved in blood pressure regulation, which makes this enzyme responsible for hypertension and a key target in the therapy of such a risk factor of cardiovascular disease. Antihypertensive peptides obtained from seafood have been extensively reviewed elsewhere [ 63 ], demonstrating that the recovery of these bioactive compounds is an efficient way of using seafood by-products. For instance, some studies have shown that peptides obtained through collagen hydrolysis from skate skin and sea cucumber can inhibit the activity of angiotensin-converting enzyme (ACE) [ 12 , 13 , 14 ], being a natural and potentially healthier alternative to synthetic ACE inhibitors available on the market.…”
Section: Bioactive Properties Of Seafood Side Stream-derived Peptimentioning
confidence: 99%
“…On the other hand, if tyrosine is replaced by phenylalanine at the C-terminus, the systolic blood pressure will decrease rapidly but only for a short time [ 67 ]. Interestingly, next to the role of marine peptides in hypertension, recent studies have also reported that they could represent a promising approach in the intervention and prevention of Severe Acute Respiratory Syndrome (SARS) virus infection, through their ACE-II inhibitory properties [ 63 ].…”
Section: Bioactive Properties Of Seafood Side Stream-derived Peptimentioning
confidence: 99%
“…SARS-CoV-2 enters cells via interactions between the Angiotensin-converting enzyme 2 (ACE2) and the Spike viral protein. Marine peptides with antiviral and anti-ACE2 activity can be an alternative tool in solving this problem (Festa et al, 2020). From this echinoderm, four peptides were also isolated from the hydrolysis of collagen.…”
Section: Echinodermata Peptidesmentioning
confidence: 99%
“…Vitamin D and calcitriol (which have known anti-inflammatory effects) are studied for their preemptive effects to help regulate angiotensin-renin mechanisms, which increase lipopolysaccharide permeability into lungs and reduce severe lung damage (Sarwar et al 2020 ; Xu et al 2017 ). Typical ACE2 inhibitors and receptor antagonists Captopril and enalapril, and iosartan and valsartan, respectively, are under study along with new inhibitory methods including single-chain variable fragments, VHH domains, nanobodies, fusion of human recombinant soluble ACE2 (hrsACE2) to an immune-adhesion molecule, and even the use of inhibitory peptides isolated from marine organisms (Festa et al 2020 ; Zhou et al 2020a , b , c ).…”
Section: Therapeutics For the Treatment Of Covid-19mentioning
confidence: 99%